2009
DOI: 10.1161/circresaha.108.192229
|View full text |Cite
|
Sign up to set email alerts
|

Human Paraoxonase Gene Cluster Transgenic Overexpression Represses Atherogenesis and Promotes Atherosclerotic Plaque Stability in ApoE-Null Mice

Abstract: Abstract-The paraoxonase (PON) gene cluster consists of the PON1, PON2, and PON3 genes, each of which canindividually inhibit atherogenesis. To analyze the functions of the PON gene cluster (PC) in atherogenesis and plaque stability, human PC transgenic (Tg) mice were generated using bacterial artificial chromosome. The high-density lipoprotein from Tg mice exhibited increased paraoxonase activity. When crossed to the ApoE-null background and challenged by high-fat diet, PC Tg/ApoE-null mice formed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
5
38
1
Order By: Relevance
“…In mice, PON1 is expressed mainly in the liver, but it can redistribute to a variety of tissues and organs including hearts by associating with HDL and secreting into the serum upon expression in the liver (Deakin et al, 2011;Marsillach et al, 2008). Indeed, we found that PON1 mRNA was absent in the heart but that its level in the liver was high, as previously reported (She et al, 2009). However, PON1 protein was detectable in the WT control hearts and increased significantly in the Ang II-induced hypertrophic hearts.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In mice, PON1 is expressed mainly in the liver, but it can redistribute to a variety of tissues and organs including hearts by associating with HDL and secreting into the serum upon expression in the liver (Deakin et al, 2011;Marsillach et al, 2008). Indeed, we found that PON1 mRNA was absent in the heart but that its level in the liver was high, as previously reported (She et al, 2009). However, PON1 protein was detectable in the WT control hearts and increased significantly in the Ang II-induced hypertrophic hearts.…”
Section: Discussionsupporting
confidence: 90%
“…Mouse genotyping was performed by PCR and agarose gel electrophoresis ( Figure 2B). The tissue-specific expression of the human PON1 (hPON1), hPON2, and hPON3 transgenes was confirmed (She et al, 2009), and we found that the mRNA of each of hPON1-3 was detected in the PC-Tg mouse hearts ( Figure 2C-E). We did not observe any difference in the heart weight (HW)/body weight (BW) ratios ( Figure 2F), cardiac morphology (left ventricular internal diameter at end-diastole, (LVID; d)) ( Figure 2G), or cardiac function, including fractional shortening (FS) and ejection fraction (EF) (Figure 2H and I), between the PC-Tg mice and their non-transgenic littermates.…”
Section: No Noticeable Cardiac Abnormalities In the Pc-tg Mice In Thesupporting
confidence: 56%
See 3 more Smart Citations